Cartes des côtes meridionales de l'Isle de Terre Neuve : comprenant les isles Royale et de Sable avec la partie du Grand Banc, où se fait la pêche de la morue - Buache, Philippe, 1700-1773 (Paris, 1741)
Colour. Prime meridians Paris and Ferro. Compass rose. Depths shown by soundings. Notes. Bar scale in French and English marine leagues. Buache offers a comparison with the English 1733 map of Mr. Popple, the outlines of which are featured in faint red over which is overlayed Buache's own map (title note and bottom note) CNS map no. 45.